Assessing the Impact of Housing Quality and WASH Access on Household Morbidity in West Sumatra, Indonesia - Saparina; Muhammad Irfan (Department of Development Economics, Universitas Sriwijaya, 2025)
Improving household health is a fundamental pillar of sustainable development, yet the transition from infrastructure provision to improved health outcomes often encounters significant structural and behavioral barriers. This study investigates the impact of housing adequacy and access to Water, Sanitation, and Hygiene (WASH) facilities on household morbidity in West Sumatra, Indonesia. Utilizing household-level microdata from the 2024 SUSENAS (National Socioeconomic Survey with a sample of 43,201, this research employs binary logistic regression to estimate the likelihood of household health complaints. The empirical findings are that housing adequacy, access to safe drinking water, and improved sanitation are significant positive determinants of household health. Conversely, the study finds that the mere physical presence of hygiene facilities and higher household expenditure are negatively associated with health status, suggesting that economic capacity alone does not guarantee well-being without corresponding health-seeking behaviors and targeted investments. Furthermore, significant rural-urban disparities and the influence of sociocultural factors, such as Minangkabau settlement patterns, highlight the complexity of the infrastructure-health nexus. These findings underscore the need for integrated, multisectoral policies that combine physical infrastructure expansion with educational interventions to promote effective hygienic practices and bridge the health-infrastructure gap in decentralized governance frameworks.